NAF-1 Inhibition by Resveratrol Suppresses Cancer Stem Cell-Like Properties and the Invasion of Pancreatic Cancer - Qin, Tao; Cheng, Liang; Xiao, Ying; Qian, Weikun; Li, Jie; Wu, Zheng; Wang, Zheng; Xu, Qinhong; Duan, Wanxing; Wong, Lucas; Wu, Erxi; Ma, Qingyong; et al. (Frontiers in Oncology, 2020)
Resveratrol is a natural polyphenolic compound with multiple biological effects, such as proliferation inhibition, anti-oxidation and neuroprotection. Besides, studies have shown that resveratrol inhibits tumor growth and migration, as well as epithelial-mesenchymal transition (EMT). However, its molecular mechanisms in tumor progression are not fully understood. Nutrient-deprivation autophagy factor-1 (NAF-1) is mainly found in the endoplasmic reticulum and mitochondrial outer membrane. It is an important genetic locus for regulating oxidative stress and autophagy. The molecular mechanism of NAF-1 in pancreatic cancer is currently unclear. The current study found that NAF-1 is positively expressed in pancreatic cancer tissue and correlated with the progression of pancreatic cancer. Furthermore, we found that NAF-1 inhibition significantly inhibits the stem cell characteristics and the invasion and migration abilities of pancreatic cancer cells. In a subcutaneous xenograft model of pancreatic cancer in nude mouse, resveratrol inhibited the expression of NAF-1, thereby inhibiting tumor growth. Resveratrol could be an effective anti-tumor drug, and NAF-1 may be a rational therapeutic target.